Responsible Mining Towards The Sustainable and Mineral Resource Development: Education Perspective - Syarifah, Abd Rahim; Suriati, Ghazali; Rohana, Abu; Ali, Eman N. (Penerbit Universiti Malaysia Pahang, 2017)
Responsible mining will initiate the sustainable and responsible mining and mineral resources development in which it is a principle that integrates the economic, social and ecological consideration to enhance the life of current and future generation will have adequate resources and opportunities. This outcome can be achieved if the mining sector adopt and apply the industry’s good practices, knowledge and resources on the sustainable development at all stages of mining including during exploration until the mine closing. This sustainable and responsible mining needs ethical and skilled professionals entering the work force in the mining industry so that the concept can be taken seriously. Thus, these professionals need to be qualified and being trained as early as in their degree education and can be continued to further at higher level of degree. Universities with collaboration of industries can compromise this through knowledge sharing in terms fundamental (concept), research and trainings.